Globalización y etnicidad en América Latina: el caso boliviano - Cristoffanini, Pablo (Diálogos Latinoamericanos, 2008)
In the last decades, Latin America has experienced a process of Americanization of its material and symbolic culture. The ostentatious symbols of this process are the proliferation and popularity of malls. On the other hand in the same period we have been witness to the revival of the ethnicity of the indigenous nations. The most emblematic example is Bolivia, where a well known Indian leader is now President of the Republic. At first sight, this process appears to be part of the antiglobalization movement. On the contrary, the central thesis of this article is that the indigenous resurgence has been possible to a large extent because of the support rendered by international groups and organisations, which in turn can be explained by the central place that original peoples have attained in the western imaginary. The renaissance of the indigenous question is a very genuine product of globalization, as is Americanization. Even the most radical versions of ethnonationalism, like the Aymara, would not be possible outside the context of globalization.